The Neanderthal teeth from Marillac (Charente, Southwestern France): Morphology, comparisons and paleobiology. Issue 138 (January 2020) - Garralda, María Dolores; Maureille, Bruno; Le Cabec, Adeline; Oxilia, Gregorio; Benazzi, Stefano; Skinner, Matthew M.; Hublin, Jean-Jacques; Vandermeersch, Bernard
Abstract: Few European sites have yielded human dental remains safely dated to the end of MIS 4/beginning of MIS 3. One of those sites is Marillac (Southwestern France), a collapsed karstic cave where archeological excavations (1967–1980) conducted by B. Vandermeersch unearthed numerous faunal and human remains, as well as a few Mousterian Quina tools. The Marillac sinkhole was occasionally used by humans to process the carcasses of different prey, but there is no evidence for a residential use of the site, nor have any hearths been found. Rare carnivore bones were also discovered, demonstrating that the sinkhole was seasonally used, not only by Neanderthals, but also by predators across several millennia. The lithostratigraphic units containing the human remains were dated to ∼60 kyr. The fossils consisted of numerous fragments of skulls and jaws, isolated teeth and several post-cranial bones, many of them with traces of perimortem manipulations. For those already published, their morphological characteristics and chronostratigraphic context allowed their attribution to Neanderthals. This paper analyzes sixteen unpublished human teeth (fourteen permanent and two deciduous) by investigating the external morphology and metrical variation with respect to other Neanderthal remains and a sample from modern populations. We also investigate their enamel thickness distribution in 2D and 3D, the enamel-dentine junction morphology (using geometric morphometrics) of one molar and two premolars, the roots and the possible expression of taurodontism, as well as pathologies and developmental defects. The anterior tooth use and paramasticatory activities are also discussed. Morphological and structural alterations were found on several teeth, and interpreted in light of human behavior (tooth-pick) and carnivores' actions (partial digestion). The data are interpreted in the context of the available information for the Eurasian Neanderthals.